CONCEPTUAL APPROACHES TO THE PROBLEM OF FORMING THE IMAGE OF SCIENCE MASTER - Irina Peretrukhina (Вестник Северо-Кавказского федерального университета)
The article considers the methods, methodological approaches to the study of image science, the present interpretation of the definition of «image ofscience», the determinants of its development. The possibilities of the formation of the image of science within a variety of modern conceptual approaches: the philosophical-cultural, economic, political, sociological, psychological, pedagogical, as well as from the point of view of reputation management and public relations. Given the author's definition of «a positive image ofscience undergraduates», describes the features of forming the image of science undergraduates.